Localization of Kv4.2 and KChIP2 in lipid rafts and modulation of outward K+ currents by membrane cholesterol content in rat left ventricular myocytes - Rudakova, Elena; Wagner, Michael; Frank, Magdalena; Volk, Tilmann (Pflügers Archiv: European Journal of Physiology, 2015)
Lipid rafts are cholesterol-enriched microdomains of the cell membrane. Here we investigate the localization of the pore forming K(+)-channel ?-subunit Kv4.2 and the ?-subunit KChIP2, underlying the transient outward K(+) current (I to), in lipid rafts in left ventricular myocytes. Furthermore, we explored the impact of membrane cholesterol depletion (using 20 mM methyl-beta-cyclodextrin (MBCD)) on K(+) outward currents. Cholesterol-saturated MBCD (20 mM) served as control. Myocytes were isolated from the left ventricular free wall of Wistar rats. The Triton X-100 (4 °C) insoluble fraction of whole cell protein was analyzed by sucrose density gradient centrifugation followed by Western blot. Kv4.2 and KChIP2 were partially detected in low-density fractions (lipid rafts). MBCD treatment (5 min) resulted in a shift of Kv4.2 and KChIP2 towards high-density fractions. K(+) currents were assessed by whole-cell patch-clamp. MBCD treatment resulted in a 29 ± 3 % decrease in I to (20.0 ± 1.6pApF(-1) vs. 28.5 ± 2.0pApF(-1), n = 15, p < 0.001, V Pip = 40 mV) within 5 min. Control solution resulted in a significantly smaller reduction in I to (17 ± 3 %, p < 0.001, p < 0.01 compared with MBCD). MBCD induced a 38 ± 9 % increase in the non-inactivating current component (I sus) (10.1 ± 0.6pApF(-1) vs. 7.6 ± 0.4pApF(-1), n = 15, p < 0.001). This effect was absent in control solution. The increase in I sus was not sensitive to 100 ?M 4-aminopyridine or 20 mM tetraethylammonium, making a contribution of Kv1.5 or Kv2.1 unlikely. In conclusion, in rat ventricular cardiomyocytes, a fraction of Kv4.2 and KChIP2 is localized in lipid rafts. Membrane cholesterol depletion results in 12 % net reduction of I to, a redistribution of the channel proteins Kv4.2 and KChIP2 and an increased delayed rectifier current.
EVALuna2:4522